The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24985/ijass.2017.29.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Testing the relationships among motivation, service quality, customer satisfaction and loyalty: A case of recreational golfers in south korea

Abstract: Competition among golf courses in South Korea for recruiting and retaining customers has increased dramatically over the years as the number of golf courses grew. Therefore, it has become important for golf course managers to understand what attracts golfers to their golf courses. The purpose of this study was to examine the relationships among motivation, service quality, customer satisfaction, and loyalty among recreational golfers in South Korea. Total 563 recreational golfers participated in this study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although there has been no consensus on the relevant dimensions to be measured, some researchers have validated the connection between service quality or experience quality, and sport tourist motivation, satisfaction, and loyalty. Woo (2017) found that service quality was significantly affected by motivation among recreational golfers. Tzetzis et al (2014) examined the relationship between sport event quality, satisfaction, and behavioral intentions constructed by Shonk and Chelladural (2008) in small‐scale sport events, showed that quality of contest directly affected visitors' word‐of‐mouth recommendation and their return intentions, and the quality of access and venue significantly influenced return intention through satisfaction.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Although there has been no consensus on the relevant dimensions to be measured, some researchers have validated the connection between service quality or experience quality, and sport tourist motivation, satisfaction, and loyalty. Woo (2017) found that service quality was significantly affected by motivation among recreational golfers. Tzetzis et al (2014) examined the relationship between sport event quality, satisfaction, and behavioral intentions constructed by Shonk and Chelladural (2008) in small‐scale sport events, showed that quality of contest directly affected visitors' word‐of‐mouth recommendation and their return intentions, and the quality of access and venue significantly influenced return intention through satisfaction.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Consequently, it is of paramount importance to analyse the user's loyalty, as it has become one of the main objectives in sports management (Cáslavová, Pecinová, Ruda and Šíma, 2018;García, Alguacil, and Molina, 2020); and examine how loyalty influences the relationship between customer satisfaction and repurchase intention (Woo, 2017;Yi and La, 2004) or the relationship between team loyalty, sponsorship awareness, attitude toward the sponsor, and purchase intentions (Biscaia, Correia, Rosado, Ross, and Maroco, 2013;Wakefield, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding studies related to perceived quality and golf, several studies have been carried out internationally (Crilley, Murray, Howat, March, and Adamson, 2002;Kuhn et al, 2019a;Kuhn, Bendesa, Wiranatha, and Oka-Suryawardani, 2019b;Woo, 2017;Wu and Ai, 2015). In Spain, studies related to golf and quality, highlight the research of Serrano (2013), Iglesias 2015, Pradas (2016) and Iglesias and Lara (2019).…”
Section: Introductionmentioning
confidence: 99%